Managing University Accreditation Documents with an Online-Based Data Collection System - Alim, Ilmam Fauzi Hashbil; Subari, Arkhan (Journal of Vocational Studies on Applied Research, 2024)
By implementing digitalization, organizations and companies can increase and maintain competitive advantage, because it can increase productivity, innovation and reduce costs. One of the activities carried out by organizations is data management, including organizations operating in the education sector, such as universities. In managing a university, there are various kinds of data that must be managed. Data on the number of students, number of research studies, number of services, etc. need to be managed well. The data is usually stored in several separate places. If managers need information, they have to collect the data from several sources and process it manually using software such as Microsoft Word or Microsoft Excel. This causes the process of searching for information to take a long time, because there are several stages that must be carried out before getting the information in question. In this study, we developed web-based data management information system in universities using Waterfall Software Development Lifecycle (SDLC) method. The information system that was developed passed the Black Box method test with 100% of the possible points. According to this outcome, every feature created is in line with the executed design.